From sexual transgression to maternal neglect. Justification of parricide al the beginning of the Chilean 20th century (Quinto Sol, 2024)
This article analyzes the representations of motherhood at the beginning of the 20th century in Chile, focusing on its emotional configuration.Through a case study of parricide, it observes how the justification of male violence added a new discourse to validate itself in the public space, from female sexual transgression to the breach of maternal duties.The symbolic recovery of the "Mater dolorosa" model -based on a religious-Christian reference- was part of a strategy to reinforce the traditional feminine ideology aimed particularly at elite women in a context in which gender norms were discussed by women in this social sector. The emotional idealization of motherhood not only implied the reinforcement of the synonymy between maternity and femininity, but also the valuation of female passivity in the face of suffering and male violence.
Keywords: gender; maternity; Mater Dolorosa; social roles